ASSOCIATION OF GINGIVAL BIOTYPE AND FLAP DESIGN CONSIDERED AT STAGE TO UNCOVERY - A RETROSPECTIVE STUDY - Minal Gopal, Tulsani; R, Subhashree. (International Journal of Psychosocial Rehabilitation, 2020)
AIM: To evaluate the association between gingival biotype and flap design consideration at the time of stage two uncovery.MATERIAL AND METHOD: A retrospective study was done in which 528 implants were placed from 1 June 2019 till 1 March 2020 were included. Data was reviewed from the patient records and analysed the data of 86,000 patients between June 2019 and March 2020 that were documented in a private institution. Statistical analysis was performed to assess the association between gingival biotype and flap design consideration at the time of stage two uncovery.Results: Gingival biotype had no significant difference when compared between males and females and different age groups. Flap design consideration had no significant difference when compared between males and females, but the difference was statistically significant when seen between different age groups. There was a statistically significant association between gingival biotype and flap design consideration at the time of stage two uncovery (p